(untitled) (Bangladesh Veterinarian, 2010)
The present study was undertaken to estimate effects of environmental factors on milk production traits in Red Chittagong Cattle (RCC). A total of 103 milk yield records of 45 RCC cows obtained between 2005 and 2009 were analysed. Actual lactation yield, lactation length, daily milk yield and dry period were estimated as 500.7 ± 19.3 kg, 259.6 ± 6.2 days, 1.9 ± 0.1 kg and 162.4 ± 7.7 days, respectively. Age and season corrected lactation yield, 305 day milk yield and daily milk yield were estimated as 605.4 ± 22.9, 677.1 ± 19.4 and 2.2 ± 0.1 kg, respectively. Sex of calf and season of birth did not significantly (P>0.05) affect production, but lactation order significantly (P<0.05) affected production except lactation length. Year of birth had no effect (P>0.05) on the traits analysed except daily milk yield (P<0.05). Calving age significantly (P<0.05) affected lactation yield but did not other traits. Cows in 5th lactation produced highest total (604.3 ± 69.3 kg) and daily milk yield (2.17 ± 1.8 kg). Cows aged 6 – 7 years had best lactation yield (576.8 ± 60.5 kg). (Bangl. vet. 2010. Vol. 27, No. 1, 18 – 25) DOI: 10.3329/bvet.v27i1.5911